Description of Common Ailments and Nonprescription Medications Found in Medication Reviews for People With Intellectual Disability. - Felkai, Chelsea; Carew, Jamie‐Lee; Newby, David; Croft, Hayley (Journal of Intellectual Disability Research, 2025)
Background: People with intellectual disability (ID) are more susceptible to experiencing minor health issues. This research describes the common ailments and nonprescription medications found in people with ID who have had a medication review performed by a credentialed pharmacist in Australia. Aims: The aims of this research were to (i) describe the common ailments found within people with ID and (ii) identify and quantify the nonprescription medications documented in medication reviews for people with ID. Method: This research conducted a retrospective analysis of medication review reports and referrals from credentialed pharmacists who have performed a medication review for a person with ID between January 2020 and January 2024. Results: A total of 80 responses and reports were obtained. The average age of the person with ID was 52 years. On average, each medication review listed 6.6 common ailments and 8.0 nonprescription medications. The highest number of nonprescription medications listed for a single individual was 26. Conclusion: This research is the first to exclusively examine common ailments and nonprescription medications found in people with ID through medication reviews. Further research is needed to confirm study findings revealing a potentially high occurrence of common ailments and nonprescription medication use in this population compared to other similar populations and notable polypharmacy for nonprescription medications.